Erratum: A Comprehensive Analysis of Dermatological Manifestations in Lower Limb Para-Athletes - Aabedi, Andre; Wang, Vera; Agrawal, Devendra K. (Archives of Clinical and Medical Case Reports, 2026)
Abstract not available in the source database.